DEPLOYMENT OF ARTIFICIAL INTELLIGENCE ON THE IMPLEMENTATION OF TEACHING AND RESEARCH PROGRAMMES OF TERTIARY INSTITUTIONS IN FCT, ABUJA, NIGERIA - Okani Doris Ugo-onyeka PhD (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: This study examined the deployment of Artificial Intelligence in the implementation of teaching and research programmes in tertiary institutions in the Federal Capital Territory (FCT), Abuja, Nigeria. Method: The study adopted a correlational survey research design. A sample of 230 respondents comprising academic staff and postgraduate students was selected using a simple random sampling technique. Data were collected using a structured questionnaire titled Artificial Intelligence Deployment and Teaching and Research Programme Implementation Questionnaire (AIDTRPIQ). The instrument was validated by experts in Educational Management and Educational Technology, while reliability was established using the Cronbach Alpha method which yielded a reliability coefficient of 0.82. Data were analyzed using descriptive statistics and Pearson Product Moment Correlation (PPMC) at a 0.05 level of significance. Results: The findings revealed that Artificial Intelligence deployment significantly influences the implementation of teaching programmes (r = 0.68, p < 0.05) and research programmes (r = 0.72, p < 0.05) in tertiary institutions in FCT Abuja. The study concluded that AI technologies enhance teaching effectiveness through adaptive learning systems, automated assessment tools, and intelligent tutoring systems. AI also improves research productivity by facilitating large data analysis, literature review automation, and knowledge discovery. Novelty: The study recommended increased funding for AI infrastructure, development of institutional policies for AI integration, and continuous training programmes to improve AI literacy among academic staff and students in Nigerian tertiary institutions.